2018
DOI: 10.1177/0957650918786148
|View full text |Cite
|
Sign up to set email alerts
|

Non-axisymmetric endwall profiling in a highly loaded compressor cascade

Abstract: Very few studies of non-axisymmetric endwall profiling in compressor have been conducted in published literatures. This study investigates the control mechanism of non-axisymmetric endwall on the flow field of a highly loaded compressor cascade and the guidelines for the design of non-axisymmetric endwall. First, CFD method was validated with existing experimental data. Then, the design method of non-axisymmetric endwall based on trigonometric function and Bezier curve was introduced. The design strategies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Liu 14 and Li 15 found that the groove near the leading edge mostly influenced the adverse pressure gradient and improved the compressor performance. Cao 16 proposed that the CEW introduced an increased spanwise inward pressure gradient, which was beneficial to the performance. Besides, Dorfner 17 optimized the endwall of a linear compressor and found that the groove structure upstream of the leading edge of the blade acted as an aerodynamic separator.…”
Section: Introductionmentioning
confidence: 99%
“…Liu 14 and Li 15 found that the groove near the leading edge mostly influenced the adverse pressure gradient and improved the compressor performance. Cao 16 proposed that the CEW introduced an increased spanwise inward pressure gradient, which was beneficial to the performance. Besides, Dorfner 17 optimized the endwall of a linear compressor and found that the groove structure upstream of the leading edge of the blade acted as an aerodynamic separator.…”
Section: Introductionmentioning
confidence: 99%
“…The diffuser with leaned vanes accelerated the flow in the diffuser inlet region and reduced the losses of incidence angle, which weakened flow separation and delayed the onset of rotating stall. Recently, nonaxisymmetric endwall contouring technology proved its effectiveness in turbines 16,17 and axil compressors [18][19][20] to suppress the secondary flow and flow separation. Zhou et al 21 performed a numerical optimization on non-axisymmetric contouring endwall for a vaned diffuser hub-side wall of a centrifugal compressor, which showed the total pressure loss of the diffuser decreased under design condition, but the stable operating range of compressor stage decreased as well.…”
Section: Introductionmentioning
confidence: 99%
“…Wang 25 studied endwall contouring and tested it in a large size research compressor with embedded stators and showed that the strategy to minimize the pressure above 90% span was best to decrease stator loss. Cao 26 studied control mechanism of CEW and found that the increased spanwise inward pressure gradient also contributed to the performance improvement. Zhang 27 studied the co-work of endwall contouring with tandem compressor and revealed that the positive of the optimum profiled endwall was to limit the extension of recirculation region in the front passage and suppress the suction corner separation in the rear passage.…”
Section: Introductionmentioning
confidence: 99%